2019
DOI: 10.1186/s41606-019-0036-4
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of sleep quality and daytime sleepiness in hemodialysis patients: a cross-sectional study from Palestine

Abstract: Background: Patients on hemodialysis (HD) commonly suffer from poor sleep quality which in turn compromises their quality of life and well as their mortality risk according to many studies. In Palestine however, no single study had emphasized the association and prevalence of sleep quality and daytime sleepiness among hemodialysis patients (HDP). Therefore, we conducted this study to determine the relationship between regular HD and the situation regarding sleep quality and daytime sleepiness in HDP. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 24 publications
(22 reference statements)
6
23
2
Order By: Relevance
“…Correlations between sleep disorders and sex in patients on dialysis result in some degree of debate. Some trials concluded that sex was neither significantly correlated with the presence of sleep disorders nor with their severity [32]; however, female sex was an independent predictor of patients being poor sleepers among 164 patients on HD who had been screened by Pai et al for sleep disorders [25]. In addition, in 227 patients on HD in Saudi Arabia, poor sleep was more significant in female patients than in male patients [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlations between sleep disorders and sex in patients on dialysis result in some degree of debate. Some trials concluded that sex was neither significantly correlated with the presence of sleep disorders nor with their severity [32]; however, female sex was an independent predictor of patients being poor sleepers among 164 patients on HD who had been screened by Pai et al for sleep disorders [25]. In addition, in 227 patients on HD in Saudi Arabia, poor sleep was more significant in female patients than in male patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…us, it is essential for healthcare professionals to recognize different aspects of poor QOL in patients on dialysis. In addition, more studies are needed to further clarify the risk factors of depression and sleep disorders and to assess the efficacy of therapeutic measures in these patients [24,[29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly a survey conducted among Canadian (22) from 2002 to 2014 indicate cigarette smoking as cause of RTA associated daytime sleepiness. Monthly income, female gender and low schooling level remained positively and independently associated with EDS as shown by the study conducted in Brazil (6) where the study conducted in An-Nahah showed no association of daytime sleepiness with any socio-demographic factors (23).…”
Section: Introductionmentioning
confidence: 89%
“…General health in these patients is affected by numerous factors, including the disease, family conditions and their attitudes and cognitions (13). Moreover, sleep disorders, anxiety, depression and social isolation reduce general health in ESRD patients (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%